Pengaruh Penggunaan Tepung Daun Sirsak (Annona Muuricatal) Terhadap Tingkat Kemasiran dan Kadar Protein Telur Itik Asin: The Effect of The Use of Soursop Leaf Flour (Anonna muuricata L.) on Graduity and Protein Levels of Salted Duck Eggs - Chandrasusilo; Nurhaeda; Nevyani Asikin; Fitriani Fitriani (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine the effect of adding soursop leaf flour (Annona Muricata L.) to the level of grit and protein content of salted duck eggs. This study used a Complete Reasoning Design (CRD) with 4 levels of treatment and 3 replications, namely P0 = no treatment, P1 = addition of 10 grams of soursop leaf flour, P2 = addition of 20 grams of soursop leaf flour, P3 = addition of 30 grams of soursop leaf flour. The results showed that with the addition of soursop leaf flour on the level of grit, no significant effect on salted duck eggs and no significant effect on protein content. The average value of the highest to the lowest level of cleanliness is P1 of (4.44), P3 of (4.39), P0 of (4.02) and P2 of (3.88). The average value of the highest salt content to the lowest is P3 of (22.85), P2 of (22.43), P1 of (22.42) and P0 of (22.40).